Keterampilan Metakognitif Siswa dalam Menyelesaikan Soal HOTS Materi SPLDV Ditinjau dari Disposisi Matematika - Laila Nur Azizah; Nining Setyaningsih (Paedagogie, 2026)
This study focuses on analyzing students' metacognitive skills in solving Higher Order Thinking Skills (HOTS) questions on two-variable linear equation systems (SPLDV) in terms of their mathematical disposition levels. This study applies a qualitative method with a descriptive approach. The research subjects were selected based on high, medium, and low mathematical disposition categories. Data were collected through mathematical disposition questionnaires, HOTS tests, and interviews. Data analysis included data reduction, data presentation, and conclusion drawing using triangulation techniques. The results showed that mathematical disposition influenced students' metacognitive skills. Students with high mathematical disposition successfully achieved the indicators of planning, monitoring, and evaluation optimally. Students with moderate mathematical disposition were able to achieve the indicators of planning and monitoring, but were not yet able to achieve the indicator of evaluation. Meanwhile, students with low mathematical disposition did not succeed in achieving the three indicators of metacognitive skills. The results of the study indicate that mathematical disposition plays a role in determining the level of students' metacognitive skills. Thus, educators need to plan the mathematics learning process that emphasizes students' thinking processes so that students' metacognitive skills can develop optimally.